ДОВГОЛІТНІ ТРАНСФОРМАЦІЇ ПЛАНКТОНУ В ГІПЕРГАЛИННОМУ БАКАЛЬСЬКОМУ ОЗЕРІ (КРИМ) ПРИ КОЛИВАННЯХ СОЛОНОСТІ - Загородня, Ю. А.; Батогова, К. О.; Шадрiн, М. В. (Marine Ecological Journal, 2023)
Plankton of the hypersaline lake Bakalskoe was studied during 2000 – 2007 and these results were summarized. Water salinity of the lake fluctuated from hypersaline to polyhaline level at that time. Variability of salinity led to faunistic changes, namely, halobionts are substituted with sea species or to the contrary way. Composition of main primary producers changed: in 2000 – 2002 - cladophora mats was most important producer – 1 – 2 order higher then phytoplankton; 2004 – 2005 – the cladophora mats were absent, phytoplankton was the main producer, primary production was much less then before; 2006 – 2007 - bottom cyano-algae-biofilms gave the main part of primary production. There was not so big species diversity in the lake but with high transformation potential: in the different years there was different species composition of zooplankton but with relatively high total abundance.